EVALUATION ON AN ENGLISH COURSEBOOK IN ONLINE LEARNING: VOICES FROM TEACHERS - Wawan Setiawan (University of Kuningan, 2021)
The COVID-19 pandemic has changed how teaching and learning is implemented in Indonesia. To prevent the possibility of spreading the virus, students learn from home through online learning. The research is aimed at investigating teachers’ voices on the suitability of coursebook in online learning and teachers’ strategies to make the materials more relevant to teaching and learning context. Data gathered from four English teachers at SMAN 1 Indramayu, a public school situated in West Java, Indonesia, through closed and open questionnaires. The results showed that the coursebook was suitable to be used in online learning despite the fact that it was first used in traditional classrooms. To meet students’ needs and expectation, teachers adapted the materials by employing several strategies such as combining the materials with other resources, redesigning, and reordering.